Prognostic Factors in Myoepithelial Carcinoma of Salivary Glands: A Clinicopathologic Study of 48 Cases. (July 2015) - Kong, Max; Drill, Esther N.; Morris, Luc; West, Lyndsay; Klimstra, David; Gonen, Mithat; Ghossein, Ronald; Katabi, Nora
Abstract : Myoepithelial carcinoma (MECA) is an underrecognized rare tumor with a diverse clinical behavior. The histologic features of this tumor are not well characterized, much less its grading, which is controversial. The objective of this study is to provide a better characterization of MECA and its prognostic factors. A total of 48 cases were retrieved from the pathology files. The cases were subjected to a detailed histopathologic, immunohistochemical, statistical, and clinical analysis. Tumors were classified as de novo MECA in 22 cases (46%) and carcinoma ex-pleomorphic adenoma (CA ex-PA) in 26 cases (54%). Tumor necrosis, high mitotic count (≥6/10 high-power fields), and severe pleomorphism were identified in 38%, 33%, and 21%, respectively. Perineural invasion, vascular invasion, and positive margins were noted in 10%, 12%, and 47%, respectively. Median follow-up was 38 months. Four patients had lymph node metastasis at presentation, 9 developed local recurrences, and 12 had distant metastases with the lung being the most common site (83%). The presence of CA ex-PA, necrosis, and vascular invasion correlated significantly with disease-free survival ( P =0.02, 0.01, 0.03, respectively). No distant recurrence was noted in all 23 patients lacking necrosis in their neoplasms (median follow-up: 44 mo). MECA is a relatively aggressive tumor that is associated with a high rate of distant metastasis (27%). Compared with de novo MECA, CA ex-PA correlates with worse clinical outcome. A grading system based on the presence of tumor necrosis should be used to identify high-grade MECA and predict its clinical behavior.